2009
DOI: 10.1080/10236660802660783
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Coating Thickness of Polymer on Chiral Discrimination of Cellulose Tris(3,5-Dimethyl Phenylcarbamate) Chiral Stationary Phase

Abstract: The influence of the coating thickness of the polymer on the chiral discrimination of cellulose tris(3,5-dimethyl phenylcarbamate) (CDMPC) chiral stationary phase (CSP) is investigated. CDMPC-CSPs with different thicknesses of polymer were prepared, and their chromatographic performances were investigated. Thinner coat of polymer will increase the interactions between the samples and the support of CSPs and decrease the selectivity of CSPs. Too thick coat of polymer will not increase the performance of CSPs si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
2
0
0
Order By: Relevance
“…The influence of coating amount on retention factor k 1 ′ could be seen in Figure 9. As shown in Figure 12, the effect of coating amount on column efficiency N was the same as that of previous studies, 22 and an excessive amount of CDMPC affected the intraparticle diffusion of the samples, lowering performance of the columns. In terms of separation factor α (shown in Figure 11B), except for B, they hardly changed with the change of coating amount, which indicated that the coating amount had little effect on the separation factor.…”
Section: Influence Of Total Coating Amountsupporting
confidence: 75%
See 1 more Smart Citation
“…The influence of coating amount on retention factor k 1 ′ could be seen in Figure 9. As shown in Figure 12, the effect of coating amount on column efficiency N was the same as that of previous studies, 22 and an excessive amount of CDMPC affected the intraparticle diffusion of the samples, lowering performance of the columns. In terms of separation factor α (shown in Figure 11B), except for B, they hardly changed with the change of coating amount, which indicated that the coating amount had little effect on the separation factor.…”
Section: Influence Of Total Coating Amountsupporting
confidence: 75%
“…In terms of separation factor α (shown in Figure 11B), except for B, they hardly changed with the change of coating amount, which indicated that the coating amount had little effect on the separation factor. As shown in Figure 12, the effect of coating amount on column efficiency N was the same as that of previous studies, 22 and an excessive amount of CDMPC affected the intraparticle diffusion of the samples, lowering performance of the columns.…”
Section: Influence Of Total Coating Amountsupporting
confidence: 75%